The Beginnings of Kibondeni college, Nairobi : a historical and sociological overview - (:unkn) unknown (My University, 2015)
The theme of this article is Kibondeni College, a corporate work of Opus Dei in Kenya, East Africa. Its focus is the pre-history, the initial stages and the development of the school which started as a service unit alongside Strathmore and Kianda Colleges. The article seeks to highlight the role of the teaching, faith and vision of St. Josemaría Escrivá with respect to hospitality work as a noble career for women, and how several ladies of Opus Dei implemented it at a difficult moment in Kenya’s history.
Studia et Documenta: rivista dell'Istituto Storico San Josemaría Escrivá vol 5 (2011): 77-130.
The theme of this article is Kibondeni College, a corporate work of Opus Dei in Kenya, East Africa. Its focus is the pre-history, the initial stages and the development of the school which started as a service unit alongside Strathmore and Kianda Colleges. The article seeks to highlight the role of the teaching, faith and vision of St. Josemaría Escrivá with respect to hospitality work as a noble career for women, and how several ladies of Opus Dei implemented it at a difficult moment in Kenya’s history.
Keywords: Catering Schools – Women; Kibondeni College; Opus Dei – Josemaría Escrivá – Kenya – 1960-1970